2012
DOI: 10.1074/jbc.m112.374462
|View full text |Cite
|
Sign up to set email alerts
|

Opposite Orientations of a Transcription Factor Heterodimer Bind DNA Cooperatively with Interaction Partners but Have Different Effects on Interferon-β Gene Transcription

Abstract: Background: Nucleoprotein complexes are frequently assumed to adopt a unique configuration. Results: ATF2-Jun heterodimers bound the interferon-␤ enhancer in two opposite orientations in association with IRF3 and HMGI. Opposite heterodimer orientations exhibited the same cooperativity of ATF2-Jun-IRF3-HMGI complex formation, but had distinct transcriptional activities. Conclusion: ATF2-Jun heterodimer orientation did not affect binding cooperativity, but affected transcriptional activity. Significance: Changes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…In mouse embryonic fibroblasts (MEFs), studies using p65/RelA knockout mice suggested that NF-κB was rate limiting for IFN transcription only under conditions of low IRF3 activation (68). Interestingly, IRF3 recruitment has been proposed to be more efficient when c-jun/ATF2 are already bound adjacent to the IRF binding site (66, 69). …”
Section: Discussionmentioning
confidence: 99%
“…In mouse embryonic fibroblasts (MEFs), studies using p65/RelA knockout mice suggested that NF-κB was rate limiting for IFN transcription only under conditions of low IRF3 activation (68). Interestingly, IRF3 recruitment has been proposed to be more efficient when c-jun/ATF2 are already bound adjacent to the IRF binding site (66, 69). …”
Section: Discussionmentioning
confidence: 99%
“…Studies using different experimental approaches in different model systems have focused on different mechanisms of combinatorial transcriptional regulation (Arnosti et al, 1996;Burns and Kerppola, 2012;Takaya et al, 2012). BiFC analysis of protein interactions on polytene chromosomes combines various aspects of these approaches by providing information about molecular interactions in genetically modified animals at high spatial resolution.…”
Section: Visualization Of Combinatorial Transcription Complex Bindingmentioning
confidence: 99%
“…were classified in different categories based on previous studies of their activation (52)(53)(54). The Cdkn1a and Ccng1 transcripts were chosen for analysis because of the evidence for a role of Keap1 in the cell cycle (41).…”
Section: Discussionmentioning
confidence: 99%
“…Chromatin binding by Keap1 and by other regulators of virus induced gene transcription, and H3K9me2 deposition, were measured by ChIP analyses at virus induced genes and cell cycle associated genes in multiple independent MEFs of each genotype. The binding proteins and H3K9me2 were chyosen for analysis because of previous studies of proteins and histone modifications that correlated with the activation or inhibition of cytokine transcription (22, 23, 53).…”
Section: Methodsmentioning
confidence: 99%